2022
DOI: 10.3233/jad-215589
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycosylation End Products Induced Synaptic Deficits and Cognitive Decline Through ROS-JNK-p53/miR-34c/SYT1 Axis in Diabetic Encephalopathy

Abstract: Background: miR-34c has been found to be implicated in the pathological process of Alzheimer’s disease, diabetes, and its complications. Objective: To investigate the underlying mechanisms of miR-34c in the pathogenesis of diabetic encephalopathy (DE). Methods: Diabetes mellitus rats were developed by incorporating a high-fat diet and streptozotocin injection. Morris water maze test and novel object recognition test were used to assess the cognitive function of rats. Expression of miR-34c were detected by fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The burst release of ROS through prolonged mPTP opening results in dissipation of mitochondrial membrane potential, organelle swelling and rupture, mitochondrial dysfunction and cell death[8, 9,41]. Syt1 has been reported to be associated with oxidative stress regulation in glioma, neuron, and diabetic encephalopathy, but direct evidence is lacking [28][29][30]. Here we demonstrated that Syt1 was abundantly distributed in the mitochondria of cardiomyocytes.…”
Section: Synaptotagmin-1 Is Suppressed By Mir-193b-3pmentioning
confidence: 70%
See 1 more Smart Citation
“…The burst release of ROS through prolonged mPTP opening results in dissipation of mitochondrial membrane potential, organelle swelling and rupture, mitochondrial dysfunction and cell death[8, 9,41]. Syt1 has been reported to be associated with oxidative stress regulation in glioma, neuron, and diabetic encephalopathy, but direct evidence is lacking [28][29][30]. Here we demonstrated that Syt1 was abundantly distributed in the mitochondria of cardiomyocytes.…”
Section: Synaptotagmin-1 Is Suppressed By Mir-193b-3pmentioning
confidence: 70%
“…Syt1-positive neurons exhibit more axonal varices which is a key feature of neuronal susceptibility to oxidative stress [29]. Both the mRNA and the protein levels of Syt1 were decreased during oxidative stress induced by advanced glycation end-products (AGEs) in diabetic encephalopathy [30]. Bioinformatics analysis suggests a strong correlation between Syt1 and oxidative stress [28].…”
Section: Introductionmentioning
confidence: 99%
“…369 In addition, miRNAs play important regulatory roles in metabolic memory-mediated neurodegenerative diseases. [370][371][372][373] For example, miR-132 is downregulated in hippocampal neurons in rats with diabetic encephalopathy, accompanied by upregulated glycogen synthase kinase (GSK)-3β and tau. miR-132 could alleviate the impairment of diabetic encephalopathy via inhibiting GSK-3β expression and attenuating Tau hyperphosphorylation.…”
Section: Cells Involved In Metabolic Memory Immune Cellsmentioning
confidence: 99%
“…Advanced glycosylation end products are usually produced by non-enzymatic glycosylation caused by hyperglycemia; they are a set of isomeric metabolites characterized by significant toxicity [7][8][9]. AGEs are difficult to remove in the body, are closely related to the occurrence and development of CVD, and are considered to be an important cause of microvascular complications and lipid mass spectrometry changes in diabetes [10].…”
Section: Introductionmentioning
confidence: 99%